Modernizing the Military: Promoting a New 'Brand Image' of the British Army, Navy, and Air Force in the Post-National Service Era, 1957–63. (July 2019) - Maartens, Brendan
The 1957 Defence White Paper is widely regarded as a milestone in British military history, not least because it heralded the end of post-war conscription or National Service. The impact of the paper on the higher aspects of Britain's defence policy, and on the nation's place in Europe and the wider world, has been well documented. Yet little is known about how the armed forces responded to the reforms with a series of large-scale military recruitment campaigns to boost their annual intake of volunteers. The gradual phasing out of conscription placed new pressures on the Army, Navy, and Air Force, and this article explores how they sought to manage the transition from a partly conscripted to an all-professional system in 1957–63. Exploring a range of promotion carried in newspapers, films, newsreels, and broadcast media, it shows how recruiters drew on prevailing ideas of youth, modernity and affluence to try to entice a new generation of volunteers to the military.